Keeping up with the prostate-specific membrane antigens (PSMAs): an introduction to a new class of positron emission tomography (PET) imaging agents - Czarniecki, Marcin; Radtke, Jan Philipp; Giesel, Frederik L. (Contemporary oncology, 2018)
Prostate-specific membrane antigen (PSMA) targeted positron emission tomography (PET) is an emerging prostate cancer imaging method, which has been reported to have a higher sensitivity and specificity than the currently approved PET imaging agents. Multiple PSMA ligands are being investigated around the world and applications range from primary tumor characterization, to local staging, biochemical recurrence, metastasis, and image-guided interventions. The most investigated PET tracers are labelled with 68-Gallium or 18-Fluoride and are discussed in this review. Additionally, 99mTc labeled PSMA agents for single photon emission computed tomography (SPECT) imaging are elucidated as an alternative method of PSMA image acquisition.
Gesehen am 25.04.2019